Improving critical thinking skills through the implementation of E-worksheets based on differentiated PjBL-STEM - Kesi Meirawati; Abdurrahman; Tri Jalmo (CV. FOUNDAE, 2025)
Background: Critical thinking is an important skill because it involves reasoning and logic in problem solving efforts. Although it is important, it turns out that students’ critical thinking skills are currently still low. Aims: This study aims to describe the practicality and effectiveness of e-worksheets based on Differentiated PjBL-STEM to improve critical thinking skills. Methods: This research is a Research and Development that refers to the Borg and Gall model. The population is all grade IX students at one of the junior high schools in Tanjung Bintang District. Research instruments were questionnaires for the needs of educators and students, questionnaires for validating e-worksheets by experts, questionnaires for responding educators and students, pretest-posttest, critical thinking skills data analysis techniques using t-test. Result: The validation results of e-worksheets for the suitability of content, attractiveness, and readability obtained an average of 88.35%, meaning that e-worksheets is valid, while the educator’s response was 98.29%, the average student response for the attractiveness and readability aspects was 96.11%, meaning that e-worksheets is practically. The results of the t-test sig.2 tailed value of 0.000 mean that the average critical thinking skills in the experimental class are higher than those in the control class. This is supported by an effect size of 1.29 which is categorized as “large”. Conclusion: Differentiated PjBL-STEM-based e-worksheets effectively improve students critical thinking skills with a significant impact on tolerance of differences in student learning readiness. Therefore, differentiated PjBL-STEM learning is important to implement in schools, especially project-based learning that is relevant to the real world.